BRICS AND CLICKS - Bold, Mary; Chenoweth, Lillian; Garimella, Nirisha K. (Online Learning, 2008)
Projections for the global economy frequently center on the BRIC countries: Brazil, Russia, India, and China. As futurists and economists alike define and re-define both formal and informal coalitions (for example, by broadening the R in BRIC to include all Eastern European economies or instead re-directing the discussion to G-8 countries or to World Trade Organization members), the education profiles of the individual nations sometimes resemble economic indicators: what is imported, what is exported, and what is the potential for expansion. Higher education, and specifically distance learning (the Clicks element of this paper), can already be charted in these terms for some nations. This paper describes the current role of distance learning in countries described as growing economies and proposes a typology for describing change as additional data become available. The paper informs readers of global developments in distance education, using the BRIC nations as examples.